Analisis Sistem Pengendalian Intern Atas Prosedur Penerimaan dan Pengeluaran Kas Pada Sekolah Ballet Royal Bali - Ni Kadek Suryadi; I Made Endra Lesmana Putra (Hita Akuntansi dan Keuangan, 2026)
This research aims to evaluate the implementation of the Internal Control System (ICS) in cash receipt and cash disbursement procedures at Ballet Royal Bali School using the COSO framework. The study is motivated by the absence of formally documented Standard Operating Procedures (SOPs) and unclear task segregation, which may increase the likelihood of recording inaccuracies and potential cash misuse. A qualitative method with a descriptive case study approach was applied. Data collection techniques included interviews, direct observation, and documentation, while data analysis followed the Miles and Huberman model. The findings indicate that internal control practices have been applied through cash recording, supporting transaction documents, and managerial authorization. However, several limitations were identified, such as the lack of written SOPs, insufficient segregation of duties, reliance on verbal authorization, and absence of structured monitoring. Based on the COSO framework, only control activities and information & communication components are adequately implemented, while control environment, risk assessment, and monitoring components remain suboptimal.